Systemic therapies in advanced epithelioid haemangioendothelioma: A retrospective international case series from the World Sarcoma Network and a review of literature. (13th March 2021) - Frezza, Anna M.; Ravi, Vinod; Lo Vullo, Salvatore; Vincenzi, Bruno; Tolomeo, Francesco; Chen, Tom Wei‐Wu; Teterycz, Pawel; Baldi, Giacomo G.; Italiano, Antoine; Penel, Nicolas; Brunello, Antonella; Duffaud, Florance; et al.
Abstract: Background: This observational, retrospective effort across Europe, US, Australia, and Asia aimed to assess the activity of systemic therapies in EHE, an ultra‐rare sarcoma, marked by WWTR1 ‐ CAMTA1 or YAP1 ‐ TFE3 fusions. Methods: Twenty sarcoma reference centres contributed data. Patients with advanced EHE diagnosed from 2000 onwards and treated with systemic therapies, were selected. Local pathologic review and molecular confirmation were required. Radiological response was retrospectively assessed by local investigators according to RECIST. Progression free survival (PFS) and overall survival (OS) were estimated by Kaplan‐Meier method. Results: Overall, 73 patients were included; 21 had more than one treatment. Thirty‐three patients received anthracyclines regimens, achieving 1 (3%) partial response (PR), 25 (76%) stable disease (SD), 7 (21%) progressive disease (PD). The median (m‐) PFS and m‐OS were 5.5 and 14.3 months respectively. Eleven patients received paclitaxel, achieving 1 (9%) PR, 6 (55%) SD, 4 (36%) PD. The m‐PFS and m‐OS were 2.9 and 18.6 months, respectively. Twelve patients received pazopanib, achieving 3 (25%) SD, 9 (75%) PD. The m‐PFS and m‐OS were.2.9 and 8.5 months, respectively. Fifteen patients received INF‐α 2b, achieving 1 (7%) PR, 11 (73%) SD, 3 (20%) PD. The m‐PFS and m‐OS were 8.9 months and 64.3, respectively. Among 27 patients treated with other regimens, 1 PR (ifosfamide) and 9 SD (5 gemcitabine +docetaxel, 2 oral cyclophosphamide, 2 others) were reported. Conclusion: Systemic therapies available for advanced sarcomas have limited activity in EHE. The identification of new active compounds, especially for rapidly progressive cases, is acutely needed. Abstract : Anthracycline‐based regimens, the standard first line treatment in advanced soft tissue sarcomas, paclitaxel and pazopanib have a very limited activity in advanced, progressive epithelioid haemangioendothelioma. In the absence of available, potentially active medical therapies, epithelioid haemangioendothelioma remains today an unmet clinical need.